Occurrence of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) Middle East–Asia Minor 1 (MEAM1) and Mediterranean (MED) in Commercial Fields of Solanum lycopersicum in Brazil - Daniel de Lima Alvarez; Daniel Mariano Santos; Pedro Hiroshi Passos Ikuno; Caroline da Cruz Martines; Sérgio Roberto Benvenga; Cristiane Müller; Renate Krause-Sakate; Regiane Cristina de Oliveira (Agronomy)
The tomato (Solanum lycopersicum) is an important crop to the economy of Brazil, and the whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) is one of the limiting factors responsible for reducing its yields. These insects are part of a cryptic species group present across almost the entire globe. The most relevant cryptic species in the world are B. tabaci MEAM1 and MED due to their capability to adapt and cause damage to vegetables, grain, and ornamental crops. The arrival of MED in Brazil through the state of São Paulo represents risks to farmers in the region due to the difficulty in managing these insects. This study assessed the occurrence of both species in tomato crops in the southeastern region of Brazil in 2020 and 2021. An amount of 79 samples containing 767 insects were collected throughout the study period, and in the cities of Sumaré (SP) and Monte Mor (SP), several samples were collected from the same location throughout the year. The insects were stored and sent for molecular analysis. The results showed an increase in MED compared to MEAM1. The presence of MED in the Minas Gerais samples was not recorded. However, a higher percentage of MED was observed in the state of São Paulo, which was detected in the municipalities of Sumaré and Monte Mor. These results possibly indicate that MED could be starting to stabilize in open tomato fields in Brazil.